Pengaruh Fasilitas Kerja, Beban Kerja, Dan Kompensasi Terhadap Kinerja Pegawai Bidang Pemadaman Pada Dinas Pemadam Kebakaran Dan Penyelamatan Kabupaten Bandung - Masripah, Resti; Rahmi, Palupi Permata (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The purpose of this research is to find out how work facilities, workload, and compensation influence the performance extinguishing field of Dinas Pemadam Kebakaran dan Penyelamatan Kabupaten Bandung employees. Multiple linear regression analysis was used, and the study population consisted of 55 employees. Employee performance is a dependent variable, and work facilities, workload, and compensation are independent variables. Data collection was carried out using observation and questionnaires. Various statistical methods, such as partial hypothesis testing, simultaneous analysis, and coefficient of determination, should be used in the study. The research results show that the work facilities partially positive and significant influences employees performance. Partial workload does a negative and insignificant influences employees performance. Compensation partially positive and significant influences employees performance. Work facilities, workload, and compensation simultaneously positive and significant influence employees performance.